Detection and putative effect of GATA4 gene variants in patients with congenital cardiac septal defects - Al-Azzouny, M A; El Ruby, M O; Issa, H A; Behiry, E G; Elsayed, N R; Fayez, A G (Cellular and Molecular Biology, 2016)
The zinc finger transcription factor GATA4, located on chromosome 8p23.1–p22, has been implicated as a critical regulator of cardiac development during embryogenesis. Mutations of GATA4 appear to be responsible for some cardiac septal defects. The aim of this work was to screen for mutations in the GATA4 gene in sample of Egyptian patients affected by isolated and non-isolated cardiac septal defects. We examined 20 patients with atrial septal defect (ASD), ventricle septal defect (VSD), atrioventricular septal defects (AVSD) and A-V canal disturbance defect and compared with examined 10 unaffected individuals as normal control. The patients were referred from Congenital Heart Disease Clinic of the Clinical Genetics department at the National Research Centre. All patients were subjected to clinical evaluation, echocardiography and karyotyping. Genomic DNA was extracted from all cases and subjected to PCR followed by direct sequencing. The predicted effect of variants was done by a variety of proper prediction tools. We detected six variants in GATA4 gene, two of them are novel variants. Predicted functional analysis of the relevant variants was performed by In silico analysis. Further confirmatory studies on familial segregation and in vitro / in vivo functional analysis are recommended to support our results.